Decent Furniture for Decent People: The Production and Consumption of Jacques & Hay Furniture in Nineteenth-Century Canada - Jacques, Denise (Université d'Ottawa / University of Ottawa, 2010)
The Canadian firm of Jacques & Hay was in business for fifty years, during which the company, if The Globe (Toronto) is to be believed, furnished the Province of Canada. This was a stunning and largely undocumented success. Jacques & Hay was one of the largest employers in the province and dominated the cabinet-making trade from 1835 to 1885. In 1871, Jacques & Hay employed 430 men and 50 women in a vertically-integrated operation that included a sawmill, two factories and a showroom. Jacques & Hay produced abundant furniture at reasonable prices. The availability of such household furnishings greatly enhanced domestic life in nineteenth-century Canada, providing scope for a more elaborate social life and allowing more people to achieve a greater sense of comfort and decency in their living arrangements.
Keywords: Furniture; Canadian; early manufacturing; consumption; social history; material history; material culture; decorative arts; Toronto